2019
DOI: 10.1155/2019/9567641
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Gene Coexpression Network Analysis Identified MicroRNA Coexpression Modules and Related Pathways in Type 2 Diabetes Mellitus

Abstract: Objective. Type 2 diabetes mellitus (T2DM) is a metabolic disease with high incidence, which has seriously affected human life and health. MicroRNA, a short-chain noncoding RNA, plays an important role in T2DM. Identification of meaningful microRNA modules and the role of microRNAs provide a basis for searching potential biomarkers of T2DM. Materials and Methods. In this study, three newly diagnosed patients with T2DM and three controls were selected for Whole Peripheral Blood RNA Sequencing to establish a mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Experiments have shown that the activation of Fc gamma R-mediated phagocytosis affects the balance of glucose metabolism. Blocking Fc gamma R-mediated phagocytosis was shown to reduce DM occurrence ( Feng et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have shown that the activation of Fc gamma R-mediated phagocytosis affects the balance of glucose metabolism. Blocking Fc gamma R-mediated phagocytosis was shown to reduce DM occurrence ( Feng et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…After the modules are identified, the correlation between the modules and clinical traits can be easily evaluated by using eigengene network methodology. This powerful tool has been commonly acknowledged and successfully applied to various diseases such as prostate cancer [6] , ischemic stroke [62] and Type 2 diabetes mellitus [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Molecular Complex Detection (MCODE) has been used to illuminate the most critical genes and finest clusters in the PPI network based on the k-core algorithm. Li et al (2015) successfully used the integration of the gene co-expression network with the PPI network for mining candidate hub genes for Alzheimer’s disease, and Feng et al (2019) performed pathway analysis for microRNAs in type 2 diabetes mellitus by integrating gene co-expression data and PPI network information. Our goal was to apply WGCNA and integrated networks to identify functionally relevant molecular pathways associated with infertility in endometriosis.…”
Section: Introductionmentioning
confidence: 99%